A proposed continuing basic Christian education program for the adult members of the Filipino-Chinese evangelical churches in Metro Manila - Son, Leonides T. (Animo Repository, 2006)
The study primarily aimed to develop a basic continuing Christian education program for the adult members of the Filipino-Chinese evangelical churches. Input in the development of the program came from the target participants of the proposed program, church leaders, and seminary professors. Results of the analysis of the input guided the conceptualization of the program in respect to important features (e.g. venue, frequency and length of meetings, medium of instruction, and choice of instructors), and program components (e.g. objectives, content, teaching strategies, and evaluation scheme). The study contributed to the literature on educational management, particularly in the area of curriculum development in a non-formal educational setting.